The distributional aspects of environmental quality and environmental policies Opportunities for individuals and households - Mackie, Alexander (OECD Green Growth Papers, 2019)
This paper reviews the empirical evidence on the socioeconomic distribution of exposure to a selection of common environmental risks such as air and noise pollution and natural hazards, and of access to amenities such as green space. It finds that there are many examples where disadvantaged groups within countries, regions or cities are exposed to greater environmental risks, and ultimately greater potential harm or damages, or have poorer access to amenities than more advantaged groups. However, this pattern is not ubiquitous, there are examples in the literature where no difference, or the opposite difference is observed. Next, the paper reviews the empirical literature on the distributional effects of environmental policies. It concludes that although the evidence on the direct effects of environmental policy varies by policy instrument type, the general lesson is that well-designed environmental policy reforms incorporating appropriately targeted compensation schemes (e.g. within existing social welfare systems) can neutralise direct negative distributional outcomes and generate progressive outcomes overall